Integrated Control of Citrus Pests in the Mediterranean Region. - Vacante, Vincenzo (Bentham Science Publishers, 2012)
This book presents a definitive exposition of citrus pests and their integrated, mostly non-chemical, control in the Mediterranean area. This is the first book on this topic written by experts from various countries around the Mediterranean region. It provides useful information about the different agricultural management methods and how they impact pest control on various citrus plant species and varieties grown in the aforementioned region. The volume also describes methods of pest sampling, monitoring practices and determining the pests' economic thresholds. Special features of this text i.